Hasmonean realities behind Ezra, Nehemiah, and Chronicles - Finḳelshṭayn, Yiśraʾel 1949- (Atlanta SBL Press, 2018)
"The book deals with key topics in Ezra, Nehemiah, and 1 and 2 Chronicles, such as the list of returnees, the construction of the city wall of Jerusalem, the adversaries of Nehemiah, the tribal genealogies, and the territorial expansion of Judah in 2 Chronicles. Finkelstein argues that the geographical and historical realities cached behind at least parts of these books fit the Hasmonean period in the late second century BCE. Seven previously published essays are supplemented by maps, updates to the archaeological material, and recent articles on the topics"--
Chapter 1: Jerusalem in the Persian (and early Hellenistic) period and the wall of Nehemiah -- Chapter 2: The archaeology of the list of returnees in Ezra and Nehemiah -- Chapter 3: The territorial extent and demography of Yehud/Judea in the Persian and early Hellenistic periods -- Chapter 4: Nehemiah's adversaries: a Hasmonean reality? -- Chapter 5: The historical reality behind the genealogical lists in 1 Chronicles -- Chapter 6: Rehoboam's fortified cities (2 Chr 11:5-12): a Hasmonean reality? -- Chapter 7: The expansion of Judah in 2 Chronicles: territorial legitimation for the Hasmoneans?
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Jews -- History -- 586 B.C.-70 A.D; Maccabees; Bible; Jews; Maccabees; Criticism, interpretation, etc; History; 586 B.C.-70 A.D